Early Toxicities After High Dose Rate Proton Therapy in Cancer Treatments - Doyen, Jérôme; Sunyach, Marie-Pierre; Almairac, Fabien; Bourg, Véronique; Naghavi, Arash O.; Duhil de Bénazé, Gwenaëlle; Claren, Audrey; Padovani, Laetitia; Benezery, Karen; Noël, Georges; Hannoun-Lévi, Jean-Michel; Guedea, Ferran; et al. (Frontiers in Oncology, 2021)
Background. The conventional dose rate of radiation therapy is 0.01-0.05 Gy per second. According to preclinical studies, an increased dose rate may offer similar anti-tumoral effect while dramatically improving normal tissue protection. This study aims at evaluating the early toxicities for patients irradiated with high dose rate pulsed proton therapy (PT). Materials and Methods. A single institution retrospective chart review was performed for patients treated with high dose rate (10 Gy per second) pulsed proton therapy, from September 2016 to April 2020. This included both benign and malignant tumors with ≥3 months follow-up, evaluated for acute (≤2 months) and subacute (>2 months) toxicity after the completion of PT. Results. There were 127 patients identified, with a median follow up of 14.8 months (3-42.9 months). The median age was 55 years (1.6-89). The cohort most commonly consisted of benign disease (55.1%), cranial targets (95.1%), and were treated with surgery prior to PT (56.7%). There was a median total PT dose of 56 Gy (30-74Gy), dose per fraction of 2 Gy (1-3Gy), and CTV size of 47.6 mL (5.6-2106.1mL). Maximum acute grade ≥2 toxicity were observed in 49 (38.6%) patients, of which 8 (6.3%) experienced grade 3 toxicity. No acute grade 4 or 5 toxicity was observed. Maximum subacute grade 2, 3 and 4 toxicity were discovered in 25 (19.7%), 12 (9.4%) and 1 (0.8%) patient(s), respectively. Conclusion. In this cohort, utilizing high dose rate proton therapy (10 Gy per second) did not result in a major decrease in acute and subacute toxicity. Longer follow-up and comparative studies with conventional dose rate are required to evaluate whether this approach offers a toxicity benefit.